PENGENDALIAN SOSIAL REMAJA PEROKOK OLEH KELUARGA DI DUSUN KENANAI DESA PIANTUS KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Naraswari, Audia; Budjang, Gusti; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe title of this research is "Social Control of Adolescent Smokers by Family in Dusun Kenanai Desa Piantus Kecamatan Sejangkung Kabupaten Sambas". A common problem in this study is how the social control of adolescent smokers by families in Dusun Kenanai Desa Piantus Kecamatan Sejangkung Kabupaten Sambas? with sub issues (1) What is the prevention of preventive family control of adolescent smokers in the Dusun Kenanai Desa Piantus Kecamatan Sejangkung KabupatenÂ  Sambas? (2) How to form the social control of teenage smoker by family repressively in Dusun Kenanai Desa Piantus Kecamatan Sejangkung Kabupaten Sambas. This study aims to determine the form of preventive and repressive social control carried out by teenage family smokers. The method used is qualitative method with descriptive analysis. The data collection tool uses observation guidelines, interviews and documentation. The results of the study were (1) preventive social control in the form of advice has been done well, it is seen with the giving of advice made by parents though with limited time. While in the form of guidance has not done well, it is seen with the lack of exemplary father to not smoke, making it a bad example for teenagers. (2) repressive social control in the form of reprimands has been done fairly well, this is seen with the provision of reprimands made by both parents, even though his own father smoking. While in the form of punishment has not been done with the maximum because parents only give punishment in the form of rebuking with words for long term without any variation of punishment and do not provide deterrent effect.Keywords: Social Control, Adolescent Smoker, Family